Role and authority: An empirical study on internal auditors in Malaysia - Umor, S.; Mahzan, N.; Zulkifli, N. (2010)
This paper addresses the relationship between the roles of the internal auditor (IA) and authority. The internal auditor's varying roles that include control oversight, decision support, risk management support, governance, system involvement, technical and intimidation, are determined by how the internal auditor himself perceives his work and the extent of which he enjoys role clarity. The results show that although the management intimidation role is dominant in explaining the variance in authority, this construct only explains l3.7 percent variance in authority. These results support the need for the Institute of Internal Auditors (IIA) to provide internal auditors with adequate interpretation of its standards to identify 'the appropriate level of authority for their roles. Considerable attention should be given to the audit charter, to specify the IA's varying roles, according to the nature and the business environment of the organization. In addition, by taking a holistic view of a what a true professional is, this study provides some empirical evidence on the association between internal auditor roles and other aspects of a true profession such as audit charter existence and employment type. The inclusion of these variables helps to conceptualize and explain the influence on the internal auditor's roles. From a practical standpoint, internal auditors may re-evaluate their actual roles, and from the various roles that they have undertaken, clarify the confusion that might have occurred concerning their roles. The results provide clear action directives for organizations concerned with the enhancement of the internal audit profession. Providing internal auditors with the authority to perform their work is perhaps the most important part of what organizations can do. Authority has the most pervasive direct and indirect influence upon internal auditors' role clarity. Thus, this study contributes towards the decision making of boards of directors, audit committees and other regulatory bodies, to augment the profession of internal auditors.